WAYS TO SAVE BUDGET FUNDS THROUGH EFFECTIVE ORGANIZATION OF PUBLIC PROCUREMENT - Rakhmatullayev Jaloliddin Mukhiddinovich (Innovation Science and Technology, 2025)
This article examines the issue of saving budget funds through the effective organization of public procurement. Measures such as the introduction of electronic platforms in the public procurement system of the Republic of Uzbekistan, improvement of the legislative framework, and encouragement of local suppliers are analyzed. The results of the study show that during 2019–2023, the share of electronic procurement increased, and the risk of corruption significantly decreased. Also, the increase in the share of local suppliers had a positive impact on the national economy. The article provides practical recommendations for increasing the transparency and economic efficiency of public procurement.